Economic Policy Uncertainty and Bank Credit Growth in Indonesia - Saputra, Sahdan; Hendri, Wira (Universitas Airlangga, 2024)
Objective: This study examines the influence of economic policy uncertainty in countries with the largest capital investments in Indonesia, such as Singapore, China, Hong Kong, Japan, the United States, Korea, and the United Kingdom, on the credit growth of commercial banks in Indonesia. Design/Methods/Approach: The sample of this study is all commercial banks in Indonesia from January 2011 to December 2022. This study uses a quantitative approach, using monthly aggregate data on credit growth of commercial banks in Indonesia and economic policy uncertainty data for each country. Hence, the number of observations in this study amounts to 144. This study uses multiple linear regression with the EViews 12 analysis tool. Findings: The findings in this study show that the influence of economic policy uncertainty in the country with the largest capital investment in Indonesia has various influences. Of the several countries that were observed in the study, Japan was one of the countries that had a significant negative impact on the growth of commercial bank credit in Indonesia. Originality/Value: This study complements several previous studies regarding the impact of economic policy uncertainty on Indonesia's micro and macro economy. Studies regarding the impact of economic policy uncertainty on Indonesia's banking credit growth are still limited. Practical/Policy implication: The findings of this study can be used as a reference for banking managers when making decisions such as credit portfolio diversification. By spreading exposure to various sectors and industries, banks can reduce risks related to economic uncertainty in specific sectors. Banking managers need to design products and services that are more creative and adaptive to help banks remain competitive and attract customer interest amidst an uncertain economic situation.